Self-assembled bovine serum albumin nanoparticles as pesticide delivery vectors for controlling trunk-boring pests - Su, Chenyu (J Nanobiotechnology, 2020)
BACKGROUND: Trunk-boring pests (TBPs) are an important type of forest pest, TBPs not only feed on the branches and trunks of trees, but also spread quarantine diseases in forests. However, because the larvae of TBPs live inside the trunk and are well concealed, prevention and control are difficult. The lack of effective control methods leads to the death of many trees in forests. In this study, a novel nanopesticide featuring high bioactivity and slow-release properties was developed to control TBPs. Thiacloprid (THI), which is commonly used to control Coleoptera species, was used as a model pesticide. RESULTS: The oleophobic properties of bovine serum albumin (BSA) were exploited to encapsulate the hydrophobic pesticide THI by self-assembly, and the size of the obtained nanoparticles, THI@BSA·NPs, was approximately 23 nm. The loading efficiency reached 70.4%, and THI@BSA·NPs could be released continuously for over 15 days, with the cumulative release reaching 93.5%. The fluorescein isothiocyanate (FITC)-labeled nanoparticles were evenly distributed in the digestive tract and body surface of a typical TBPs, M. alternatus, and the stomach and contact toxicities increased by 33.7% and 25.9%, respectively, compared with those of free THI. Furthermore, the results showed that the transport efficiency of THI@BSA·NPs was highest at a concentration of 50 μg/mL, and the THI@BSA·NPs content in the trunk, from to lower to higher layers, was 8.8, 8.2, 7.6, and 5.8 μg/g. At the same time, THI@BSA·NPs also exhibited high transport efficiency in dead trees. CONCLUSION: The transport efficiency and toxicity of the active ingredients are the key factors for the control of TBPs. This work provided idea for the application of biological delivery system encapsulated hydrophobic pesticides. The novel self-assembled THI@BSA·NPs have promising potential for sustainable control of TBPs. [Image: see text]